2001
DOI: 10.1021/ac0104680
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Based Microimmunoassay

Abstract: A small-volume heterogeneous immunoassay system is demonstrated in microchannels exploiting magnetic manipulations of small paramagnetic particles (1-2-microm diameter). The small-diameter particles help to create a high surface-area-to-volume ratio that generates the sensitivity for the small detection volumes. Flow characteristics of the magnetically formed packed bed within the channel allow the assay to be carried out quickly (minutes) while passing appropriate volumes of both samples and reagents (microli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
164
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 22 publications
0
164
0
Order By: Relevance
“…In another study, a small-volume heterogeneous immuno-assay was demonstrated using both classical fused-silica capillaries and glass microfluidic chips (Hayes et al 2001b). Figure 5 is a schematic diagram of the experimental configuration.…”
Section: Magnetic Beads As Solid Phases In Heterogeneous Assaysmentioning
confidence: 99%
“…In another study, a small-volume heterogeneous immuno-assay was demonstrated using both classical fused-silica capillaries and glass microfluidic chips (Hayes et al 2001b). Figure 5 is a schematic diagram of the experimental configuration.…”
Section: Magnetic Beads As Solid Phases In Heterogeneous Assaysmentioning
confidence: 99%
“…The boom in microfluidics, which began about 20 years ago, brought with it ideas about incorporating magnetic particles into various microfluidic devices [6][7][8][9] . This offers additional benefits compared to batchtype processes, such as reduced sample and reagent volumes, faster reaction times, the possibility to engineer the design of a chip to control particle mobility, and integration of various processes into a unified system 5 .…”
Section: Introductionmentioning
confidence: 99%
“…8 The initial feasibility studies [9][10][11] in this regard have been mostly empirical 12 and there are few comprehensive models available that describe the interaction between target species and magnetic particles. 5 We therefore conduct a fundamental investigation of the mechanics of magnetic separation on a microfluidic platform using threedimensional numerical simulations.…”
Section: Introductionmentioning
confidence: 99%